How Do Industries and Firms Respond to Changes in Local Labor Supply? - Dustmann, Christian; Glitz, Albrecht (Journal of Labor Economics, 2015)
This paper analyzes how changes in the skill mix of local labor supply are absorbed by the economy, distinguishing between three adjustment mechanisms: wages, expansion in size of those production units using the more abundant skill group more intensively, and more intensive use of the more abundant skill group within production units. We contribute to the literature by analyzing these adjustments on the firm rather than industry level, using German administrative data. We show that most adjustments occur within firms through changes in relative factor intensities and that firms entering and exiting the market are an important additional absorption mechanism.